Variety and Planting Density Effects on Grain and Fodder Yield of Groundnut, Ghana - International Institute of Tropical Agriculture (International Food Policy Research Institute, 2019)
Groundnut is the most important food and feed crop in West Africa. Grain and fodder yields on farmers field in Ghana are low due to limited use of improved varieties and inappropriate agronomic practices such as low planting densities. An on-farm was conducted over a three-year period to evaluate the effect of plant density on grain and fodder yields of improved groundnut varieties in northern Ghana.